Inquiring Arabic-Islamic Debatable Terms to ChatGPT: Will it Take a Side? - Arifianto, Muhammad Lukman; Thoriquttyas, Titis; Izzudin, Iqbal Fathi (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
In this paper, we argue that, as a powerful artificial intelligence (AI) language model, ChatGPT can be used to provide sufficient responses to questions regarding controversial Arab–Islamic terms. Therefore, this study aimed to examine the responses generated by ChatGPT regarding these terms, which are often debated by the community. By relying on a combination of content and sentiment analysis, we analyzed ChatGPT's response through the specific prompts submitted. The result shows that ChatGPT can provide sufficient and promising explanations regarding two concepts that are still considered debatable today, Jihad and Bid'ah in particular. Furthermore, the explanations generated from this AI language model are relatively balanced and moderate because they present multiperspective answers. In its conclusion part of each response, ChatGPT always warns that these terms described are labeled